Scanning tunneling microscopy studies of the Fe3O4(001) surface using antiferromagnetic probes - SHVETS, IGOR; MURPHY, SHANE; MARIOTTO, GUIDO (My University, 2003)
We have studied the (001) surface of a Fe3O4 single crystal using low-energy electron diffraction (LEED), Auger electron spectroscopy (AES) and scanning tunneling microscopy (STM). The STM measurements were performed using a novel tip of antiferromagnetic MnNi alloy. Atomically resolved STM images provide evidence of a surface terminated at the octahedral plane, with rows of Fe cations running along the ?110? crystallographic axes. Two different kinds of Fe cations with a separation of 6 ? were imaged, while the periodicity between Fe cations of the same kind is about 12 ?. We propose an interpretation of the anomalous corrugation observed in terms of a spin polarized effect, resulting in magnetic contrast between Fe2+ and Fe3+ ions in octahedral coordination.
PUBLISHED
Keywords: Physics; LEED analysis